Islam in world history - Douglass, Susan L. (Susan Lynn), 1950- author. Link Link
1 online resource (206 pages)
Keywords: Islam in World History examines the emergence and development of Islam as a world religion in the Abrahamic tradition and the unfolding of Muslim society and civilization over fourteen centuries.In contrast to the usual recital of the rise of Islam as a "new" religion, this book looks at the religious, geographic, and civilizational context in which Islam emerged and became a religiously, ethnically, and culturally diverse society deeply connected with hemispheric networks and exchanges in Afro Eurasia and ultimately a global religious community. The book addresses the development of institutions and social structures that came to characterize Muslim societies over the long term, with emphasis on their diverse expressions in various regions. The chronological approach, which analyzes the political history of Muslim society, allows for deeper understanding of how Islamicate civilization continued to develop and spread despite the fragmentation of the unitary state and its mixed record of adherence to Islamic ideals.By addressing common questions and misperceptions over the long run of Islamic history to the present day, this book is the perfect resource for all students who study religion and the history of Islam across the world.